Are Ophiolitic Substrates Drivers for Reticulate Evolution in Armeria (Plumbaginaceae)? - Manuel Tiburtini; Salvatore Tomasello; Eleonora Manzo; Luca Sandroni; Thomas Abeli; Lorenzo Peruzzi (Ecology and Evolution)
ABSTRACT Ultramafic substrates can play a role in fostering ecological adaptation and microevolutionary dynamics. The Armeria denticulata complex includes two flowering plant species (A. denticulata and A. saviana): the former is a strict serpentinophyte endemic to Tuscany and western Liguria, while the latter grows on limestone/jasper in a small area of southern Tuscany. Intriguingly, northern Apennine populations of A. arenaria subsp. praecox, a subspecies otherwise endemic to the western Alps, grow on ophiolites. Finally, the central‐southern Italian endemic A. gracilis is instead linked to limestone. We aimed at understanding whether substrate specificity and/or hybridization promoted speciation in the A. denticulata complex, despite similar ecological conditions failing to cause speciation in the nearby A. arenaria. We used Genome skimming and Illumina sequencing to assemble plastomes (152 kb) and data from the nuclear genome (ribosomal DNA subunits and 36 single‐copy markers; 27 kb in total) used to infer phylogenies and evaluate different reticulate evolution scenarios by calculating gene tree probabilities under the Coalescent model. The phylogenomic analyses were complemented by morphometric data using a matrix of 134 individuals × 27 characters. Morphometric data were analyzed both by fitting a Gaussian Mixture Model to compute population‐wise Jensen–Shannon Distances and a Neighbor‐Net network, and by inferring a standard linear discriminant analysis. Both morphometric and phylogenomic results suggest A. saviana is a species of homoploid hybrid origin, involving A. denticulata s.str. (ovule donor) and A. gracilis (pollen donor). A single population of A. denticulata from inner Tuscany (Monte Ferrato) could have originated from an introgression/hybridization event between A. denticulata s.str. (pollen donor) and A. arenaria subsp. praecox (ovule donor). Accordingly, our results suggest that substrate specificity and hybridization/introgression prompted microevolutionary processes in the Armeria denticulata complex.